Working, Housing: Urbanizing The International Year of Global Understanding - IYGU - Robinson, Jennifer (SpringerBriefs in Global Understanding, 2016)
Urban Geography / Urbanism (inc. megacities, cities, towns); Labor Economics; Human Geography; Regional Development